Terapia Respiratoria como atención primaria en el tratamiento del asma bronquial de origen atópico en pacientes de 5 a 7 años Parroquia La Unión Cantón Babahoyo periodo mayo a octubre - Ramírez Ramos, Adriana Karina (2018)
The purpose of the research work is to analyze respiratory therapy as primary care in the treatment of bronchial asthma of atopic origin in patients from 5 to 7 years old; and perform specific respiratory therapy techniques to control the disease and reduce the risk of death in patients. In the present study the deductive method was used for the scope of the problem resolution, also considering the background and objectives of the work, a qualitative and quantitative approach was also carried out, through which the process of the therapy treatments is known Respiratory disease of primary care of bronchial asthma of atopic origin in patients aged 5 to 7 years to identify the process of it and how to help counteract the disease with excellent care. Through the present study, the results acquired were analyzed through statistical data that indicate the veracity of the study. In the field investigation, it was possible to identify a series of situations that largely affect bronchial asthma of atopic origin, the economic problems they have, and the little access to free care with qualified specialists to control the disease, it is recommended that the corresponding authorities encourage specialized care by specialists in the area to provide respiratory therapy and free treatments in which they help to maintain calm in the inhabitants to combat bronchial asthma of atopic origin and reduce the risk of death in children.